1997
DOI: 10.1007/bf02414114
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of plutonium in the soil and the possibilities of identifying sources of contamination

Abstract: Because of its high radio toxicity, the long lifetime of the main isotopes of plutonium and the long time that it remains in biological systems, a study of the content and nature of the distribution of plutonium in the environment is of considerable importance in radioecoiogy. In addition to data on the plutonium concentration in natural systems [1][2][3][4][5][6], information on the isotopic composition is also of considerable value [7][8][9][10][11][12], since this is an important characteristic when establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Erdmann et al (16) determined Pu isotopes in some soil samples from the Chernobyl region by resonance ionization mass spectroscopy (RIMS) and found that the abundances of 239 Pu and 240 Pu were 66.9 ((4)% and 25.3 ((2)%; we calculated the 240 Pu/ 239 Pu atom ratio as 0.377 ( 0.037. Belyaev et al (17) reported the 240 Pu/ 239 Pu ratios determined by mass spectrometry for three soil samples collected from the 10-km zone (0.350) and 30-km zone (0.303 and 0.300) of Chernobyl. Boulyga et al ( 18) analyzed a single hot particle originating from the Chernobyl reactor by means of solid-state nuclear track detectors.…”
Section: Resultsmentioning
confidence: 99%
“…Erdmann et al (16) determined Pu isotopes in some soil samples from the Chernobyl region by resonance ionization mass spectroscopy (RIMS) and found that the abundances of 239 Pu and 240 Pu were 66.9 ((4)% and 25.3 ((2)%; we calculated the 240 Pu/ 239 Pu atom ratio as 0.377 ( 0.037. Belyaev et al (17) reported the 240 Pu/ 239 Pu ratios determined by mass spectrometry for three soil samples collected from the 10-km zone (0.350) and 30-km zone (0.303 and 0.300) of Chernobyl. Boulyga et al ( 18) analyzed a single hot particle originating from the Chernobyl reactor by means of solid-state nuclear track detectors.…”
Section: Resultsmentioning
confidence: 99%
“…i Belyaev et al (1997); reference date 1 May 1986. j Kelley et al (1999). The A 0 and A 1 horizons were collected from 30 Â 30 cm and 20 Â 20 cm areas, respectively.…”
Section: Samplesmentioning
confidence: 99%
“…We propose to use the isotopic ratios of the other plutonium isotopes to estimate the initial 241 Pu content. To check the accuracy of this estimate, we have applied the method to measured literature values for a thermonuclear weapons test [9], and for the Chernobyl accident where we adopt the numbers obtained by [10] given by [2]. Additionally, we have simulated thermal neutron irradiation of 238 U.…”
Section: Introductionmentioning
confidence: 99%